Synanthropization of the Baltic-type raised bog “Roby” (NW Poland) - Sotek, Zofia; Grzejszczak, Grzegorz; Stasińska, Małgorzata; Malinowski, Ryszard (Biodiversity: Research and Conservation, 2015)
Raised and transitional peat bogs, despite their considerable resistance to synanthropization, as a result of anthropogenic transformations are exposed to the colonisation by alien species. One of them is the peatland “Roby”, where, in the years 2007-2009 and 2014, floristic, phytosociological and soil studies were carried out in order to record the signs of ongoing synanthropization. Conducted observations and analyses indicated that the expansion of willows has taken place and at present they occupy a large part of the bog, encroaching into bog birch forest and successfully competing with Myrica gale. Progressive peat mineralisation and constructed surfaced roads within the bog, contributed to the appearance and wide distribution of synanthropic species, such as: Urtica dioica, Impatiens parviflora and Spiraea salicifolia. Raised bog communities and their characteristic species occur on a few fragments of the bog, in north-western part, where water regime is shaped mainly by precipitation and peat deposit is fairly well-preserved. At the same time, in the patches of these communities, a distinct unfavourable increase in the share of Molinia caerulea is observed.